CHARACTERISTICS OF FISHBALL ON VARIOUS CONCENTRATION OF CARRAGEENAN FROM DIFFERENT HARVEST TIME OF KAPPAPHYCUS ALVAREZII - NOOR ASIKIN, ANDI; KUSUMANINGRUM, INDRATI; HIDAYAT, TAUFIK (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: This paper investigates the effect of carrageenan from various harvest times on fishball characteristics. The harvest time consists of three different periods (40 days, 45 days, and 50 days) from Bontang Coastal, East Kalimantan, Indonesia. Methods: The carrageenan fortified to fishball used two concentrations that were 0.25% and 0.5%.The proximate analysis, including moisture, ash, protein, fat, and carbohydrate, showed significantly different (p < 0.05). The texture analysis showed that there was significantly different (p > 0.05). Results: The fishball adding carrageenan from different harvest time of seaweed also had a significantly different of sulfate content and crude fiber content (p < 0.05). The lowest water activity obtained on the fishballs adding 0.25% carrageenan from 50 days ages harvested. Conclusions: In this research, the fishball adding 0.25 carrageenan from 50 days ages was the best treatments based on the highest of protein content and the lowest of water activity.